MENINGKATKAN HASIL BELAJAR BIOLOGI MENGGUNAKAN LKS WORD SQUARE DISERTAI PRAKTIK LABORATORIUM DI MTs Al-ASROR TAHUN PELAJARAN 2011/2012 - Muarif, Moh.; Achyani, Achyani (Bioedukasi Jurnal Pendidikan Biologi, 2012)
The aim of the research to implement of worksheet word square with laboratory practice are to improve  study result of  student in grade VIII at MTs Al-Asror  year education  2011/2012 the subject matter  living systems of plants. The method in this research  was classroom  action research and  the subjeck of research is student at VIII MTS Al-Asror. The research indicated that more than 75 % student can finish the examinition. The data gaided by observation and  tes technique, and then  analysed  by using discriptif data analysed technique. The result of the analysis, showed  that  aim of worksheet word square with laboratory practice  are to increase the study result of student. Kata Kunci: model word square, praktik laboratorium, hasil belajar siswa.